Managing the risk of workplace stress : health and safety hazards - Clarke, Sharon, 1968- (Routledge, 2004)
This book takes a risk management approach to stress evaluation in the workplace, offering practical guidelines for the audit, assessment and mitigation of workplace stressors and providing a comprehensive source of theoretical and practical.